ANALISIS YURIDIS PERBUATAN MAIN HAKIM SENDIRI PADA PELAKU YANG DIDUGA MELAKUKAN TINDAK PIDANA DIKAITKAN DENGAN ASAS PRADUGA TIDAK BERSALAH - Liza Afriani; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Vigilante (Eingenrechting) which means taking the rights without the use of the tools of government power, vigilante action almost always runs parallel to violations of the rights of others, and is therefore not allowed. In the criminal procedure law which regulates the presumption of innocence, this principle explains that a person is considered innocent before a court decision has permanent legal force. So the existence of vigilante violations against the presumption of innocence. Then the act of vigilante (eigenrechting) itself has not been specifically regulated and clearly stated in Indonesian legislation. This study aims to first find out how the criminal provisions against vigilante acts, second to find out how to apply the presumption of innocence principle to several vigilante cases in Indonesia.This type of research is normative legal research, where this research is conducted by examining the principle of the presumption of innocence contained in the Criminal Procedure Code which is associated with vigilante action. This research uses descriptive research, because the author intends to provide a clear and detailed description of the provisions of the criminal act of playing rights alone and the application of the presumption of innocence to the perpetrator who is suspected of committing a criminal act.The results of this study can be concluded that the application of the presumption of innocence is still lacking in society and law enforcers because there are no specific regulations regarding vigilante actions that can threaten vigilante perpetrators and the presumption of innocence has not been well and thoroughly socialized. . If you look at the existing cases as well as several judges' decisions or jurisprudence, if there is an act of vigilantism, the provisions of the Criminal Code used to threaten vigilante perpetrators are used Article 170 of the Criminal Code regarding beatings and article 351. Criminal Code regarding persecution.Keywords: vigilante, presumption of innocence, perpetrators of criminal acts